Pasal 156 KUHAP Ditinjau Dari Asas Audi Et Alteram Partem - Putra, Oulia (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: Criminal procedural law is part of criminal law, while the principle of Audi Et Alteram Partem is one part of the criminal procedural law, commonly also known as the principle of balance, in court decisions there is a duplik istila or refutation from the defendant to plaintiff. Purposes of the Research: The purpose of this study is to examine the position of duplik in the practice of criminal procedural law. Methods of the Research: This research uses normative juridical research methods, commonly known as legal materials, normative legal research is a research that examines literature materials in the form of books and laws that have existed before, normative legal research is also known as docrinal legal materials. Results Originality of the Research: The results of this study show that the position of duplik in the trial is very low because it clashes with article 156 of the Criminal Procedure Code which does not justify the existence of duplex in making decisions by judges, so that the defendant through his legal representative cannot file objections and release himself in order to get justice.